Indigenous Course Requirements: A Liberal-Democratic Justification - Tanchuk, Nicolas; Kruse, Marc; McDonough, Kevin (Philosophical Inquiry in Education)

(untitled) (Canadian Philosophy of Education Society, 2018)
In Canada, several universities have recently implemented course requirements in Indigenous studies as a condition of graduation, while others are considering following suit. Policies making Indigenous course requirements (hereafter ICRs) compulsory have caused considerable controversy. According to proponents, a main purpose of ICRs is to address historical wrongs and to foster a more complete understanding of the ongoing relationship between Indigenous and non-Indigenous citizens. According to critics, making such courses compulsory effectively imposes illiberal restrictions on university students and faculty by limiting the epistemic aim of free inquiry, while wrongly prioritizing concern for the welfare of one social group over others. In this essay, we propose a liberal-democratic justification for ICRs that addresses these two worries about the ideals that may underwrite these courses. We argue that ICRs can be justified in liberal democratic terms insofar as they foster knowledge of what John Rawls refers to as ‘the constitutional essentials’ and remediate civic forms of what Miranda Fricker refers to as ‘epistemic injustices’. Universities, we claim have highly plausible role responsibilities to promote the civic epistemic aims identified by Rawls and Fricker, which are especially weighty due to the power university degrees confer, as part of the formation of a “democratic elite”. We then defend this line of argument against objections on the basis of academic freedom, by arguing that universities have reasons, internal to the search for truth to champion the political aims we identify.